Reaction of abaca hybrid BC2–7 (BANDALA) to bunchy top virus isolates in Eastern Visayas, Philippines - Jofil A. Mati-om; Ruben M. Gapasin; Robelyn T. Piamonte (Annals of Tropical Research)
The Institute of Plant Breeding at the University of the Philippines, Los Baños (IPB–UPLB) developed the abaca hybrid BC2–7 (BANDALA) to tolerate the BTVs that are prevalent throughout the Philippine archipelago. The reaction of this abaca hybrid BC2–7 (BANDALA) was tested with the different isolates of BTVs prevalent in the Eastern Visayas Region in the Philippines to confirm its resistance. In this study, the reaction of abaca hybrid BC2–7 (BANDALA) to four BTV isolates was evaluated and compared to the abaca varieties Inosa and Pacol. Based on disease incidence, all BTVs isolates infected 100% of Inosa plants but none of the abaca hybrid BC2–7 (BANDALA) and Pacol. The Leyte BTVs isolate produced symptoms in Inosa at 26–days after inoculation (DAI), Southern Leyte at 30–DAI, Biliran at 32–DAI and Samar at 38–DAI, while no symptoms were observed in abaca hybrid BC2–7 (BANDALA) and Pacol. Both the abaca hybrid BC2–7 (BANDALA) and Pacol showed high resistance to BTVs, whereas Inosa was highly susceptible. BTVs were detected from the plant samples using Polymerase Chain Reaction (PCR) with primers BBT–1 and BBT–2. Positive bands were detected from the Inosa inoculated with Leyte and Southern Leyte isolates at 5–DAI, Samar at 6–DAI, and Biliran at 7–DAI. The study confirms that abaca hybrid BC2–7 (BANDALA) and Pacol are highly resistant to all BTV isolates found in the Eastern Visayas Region of the Philippines.